Evaluation and comparison of the functional properties of flour from dehulled and undehulled mungbeans - Langaman, Doqueza S.; Galvez, Flor Crisanta F. (1999.)
Mungbean was utilized to produce two types of flour--dehulled and undehulled mungbean flurs. The dehulled and undehulled mungbean flours were milled using the PhilRice Flourmill. Percent recovery of the dehulled and undehulled mungbean flours were approximately 75% and 96% respectively. The two types of flour were subjected to various tests to evaluate their functional properties using all purpose flour as standard reference. For the tests where quantifiable values were obtained, such as bulk density, water absorption capacity, viscosity and fat absorption, the dehulled mungbean flour ranked the highest. In the test for solubility, both the dehulled and undehulled mungbean flours exhibited solubility at wider pH range than all purpose flour. For dough formation test, only all purpose flour showed formation of dough. Moreover, all purpose flour exhibited gelation at lower concentrations compared with undehulled mungbean flour while dehulled mungbean flour showed no gelation at all concentrations. Through physical inspection, the color of dehulled mungbean flour was gauged to be cream while undehulled mungbean flour exhibited a greenish cream color. Crude protein contents were 25.2%, 22.7% and 12.7% while moisture contents were 6.25%, 10.0% and 11.1% for dehulled mungbean flour, undehulled mungbean flour and all purpose flour respectively.
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Mung bean flour